If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying lx + 3l = 7 Reorder the terms: 3l + lx = 7 Solving 3l + lx = 7 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Reorder the terms: -7 + 3l + lx = 7 + -7 Combine like terms: 7 + -7 = 0 -7 + 3l + lx = 0 The solution to this equation could not be determined.
| 5-3x=2x+9 | | 8a-9=5a+21 | | 5y+2=3y-8 | | 4m-6m-3=9 | | 9x-88=56+1x | | 4t+7=7t+7 | | 8y-24=56 | | 12t-12=13t+33 | | 8y-18=56 | | 5y-7=4y+8 | | 8y-12=56 | | w+4=-2 | | 8y-6=56 | | 3y+8=2y+9 | | 18-8y=56 | | m-3=-4 | | 9y-6=7y+10 | | y-7=9 | | 12-8y=56 | | 3y+1=2y-4 | | 6-8y=56 | | 7x-28=4x-10 | | x-13=2x+11 | | 7x+15=-3-2x | | .5x^2+2x-70=0 | | x-15=2x+11 | | 0.02(-7y-9)+0.7y=-0.9 | | 5m-3=4m+12 | | 13x-29=31-7x | | 2x-20=9x-6 | | -3x+2(-3x-7)=-21-2x | | 10a-5=7a-2 |